Determinants of Nutritional Status, Weight Gain, and Utilization of Health Services in Toddlers: A Literatur Review - Babby Ika Pratiwi; Syahrial Syahrial; Frima Elda (Indonesian Journal of Global Health Research, 2026)
Nutritional problems in toddlers, such as stunting and underweight , as well as non-compliance in growth and development monitoring remain major public health challenges. Participation in health services such as Posyandu and other determinants that influence nutritional status need to be identified more deeply to determine appropriate interventions. This study aims to synthesize current research on the determinants of nutritional status, successful weight gain, and factors that influence the utilization of toddler health services. The method used is a literature review by searching for articles online through the Google Scholar database (13,430 articles), ScienceDirect (6,674 articles), and PubMed (499 articles). The article search used the keywords "weight gain in toddler," "toddler nutritional status , " and "Health Service Utilization in Toddlers" articles published within the last five years (2020–2025). The data analysis process went through the process of organizing , synthesizing , identifying , and further analyzing until 10 selected research articles were obtained. The research design analyzed mostly used a cross-sectional and descriptive analytical approach, with study locations covering various regions in Indonesia and one international comparative study. The results of the study show that low maternal education is the dominant determinant factor in the incidence of underweight And stunting . Key biological risk factors include a history of low birth weight (LBW), incomplete immunization status, and a history of infectious diseases such as tuberculosis and diarrhea . In terms of services, the frequency of visits to integrated health posts (Posyandu) and nutritional counseling are significantly associated with normal nutritional status. Furthermore, the effectiveness of utilizing health data for prevention is crucial. stunting influenced by the level of education and time allocation of Posyandu cadres. The nutritional status of toddlers is influenced by a complex array of factors , including parental characteristics (especially maternal education), the child's health history (immunizations and infections), and active participation in Posyandu (Integrated Health Posts). Nutrition improvement interventions must integrate maternal education, infectious disease prevention, and capacity building for health workers.